Tradisi Kabhelaino Lambu pada Etnis Muna di Kecamatan Katobu Kelurahan Raha II Kabupaten Muna (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2022)
The Kabhelaino Lambu tradition is a tradition of the Muna tribe used in building a new house with the aim of organizing the community's way of life. The objective of this study is to understand the stages of implementation and the symbolic meanings contained in the tradition. The method used in this study is a qualitative descriptive method with data collected through purposive sampling. The results of the study show that the implementation stages of Kabhelaino Lambu consist of three stages: kasolono wite, kaghondono gholeo metaa, and kabhelaino lambu. In addition, there are several symbols used in this tradition such as white cloth, village chicken eggs, a fairly large stone, a container of clean water, sand, and cement.